Planning for the Construction of a Solar Power Plant in Vaname Shrimp Ponds in Sungai Kuruk III Village, Seruway District, Aceh Tamiang Regency - Fitri, Ameliya Tiara; Dalimunthe, Muhammad Erpandi (Universitas Nusa Putra, 2024)
The construction of a Solar Power Plant (PLTS) in the Vaname Shrimp Pond, Sungai Kuruk III Village is an efficient solution in overcoming excessive electricity consumption in vaname shrimp cultivation. With the majority of the population working as fishermen and shrimp farmers, shrimp farming requires significant electricity consumption for lights, water pumps and windmills. PLTS is an efficient and sustainable solution by utilizing abundant solar energy in coastal areas. This research uses 28 solar modules with a capacity of 500 Wp, 23 batteries, an inverter with a power of 3,000 watts, and a Solar Charge Controller (SCC) with a capacity of 350 A. Thus, the implementation of PLTS is expected to reduce dependence on PLN electricity while still increasing and maintaining energy productivity as well as maintaining environmental sustainability in vaname shrimp cultivation.